Contemporary Scenario of Participatory Social Work Research in Rural India - Soundari, Hilaria (Participatory Social Work: Research, Practice, Education, 2019)
Rural India, holding 68.84% of its population as per the census of 2011 (Office of the Registrar General & Census Commissioner, 2011), stands with an outstanding model of participatory practices in social work research. As the “we feeling” is common among the rural people, indeed it becomes more feasible to enable them to participate in the research process. Based on the divergent socio-economic and cultural background of the rural Indian situation, choosing the best research practices becomes a herculean task. It may certainly enable the bringing into the limelight the struggles and strengths of the marginalized and less privileged of the rural society. The present study strives in identifying the relevant research tools for rural population, which is relatively open to the participatory research approach. It highlights the relevance and suitability of adopting these methods in social work research, especially the collaborative research practices, combining the researcher and service users’ perspective which are found to be more effective and informative. The various constraints and difficulties faced by the researchers also are portrayed and examined in relation with the rural study at the grass root level.